Internship under the framework of bilingualism for peace at Institución Educativa El Sabanal (2023)
This paper describes the Internship process performed at Institución Educativa El Sabanal. This process was carried out in Beginner, the first level of the Bilingualism for Peace program. The main purpose of this internship was to develop important 21st Century Skills for students, such as communication, collaboration, creativity and critical thinking. Furthermore, this internship also aimed to provide students with meaningful topics which they could experience in their real contexts, reflect about them and develop a deeper understanding. In order to so, Project-based Learning and Critical Literacy were used for the designing and planning of the lessons. This internship report details the context of the process, methodologies and strategies that were used, results, conclusions and recommendations, and limitations and implications for professional development.